2021
DOI: 10.3390/cells10102764
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Mutational Profiling of Hematopoietic Progenitor Cells and Circulating Endothelial Cells (CECs) in Patients with Primary Myelofibrosis

Abstract: A role of endothelial cells (ECs) in Primary Myelofibrosis (PMF) was supposed since JAK2 mutation was found in endothelial precursor cells (EPCs) and in ECs captured by laser microdissection. By Cell Search method, the circulating endothelial cells (CECs) from 14 PMF patients and 5 healthy controls have been isolated and compared by NGS with CD34+Hematopoietic stem and progenitors cells (HSPCs) for panel of 54 myeloid-associated mutations. PMF patients had higher levels of CECs. No mutation was found in HSPCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…These findings appear to confirm the origin of PMF as multipotent CD34+ HPSCs. The most frequent mutations concern driver genes such as JAK2 and non-driver genes such as ASXL1 , IDH1/2 , SRSF2 , EZH1 [ 41 ]. Further studies confirm a similar mutational profile in circulating free DNA (cfDNA) and in paired granulocyte DNA obtained from the plasma of PMF patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings appear to confirm the origin of PMF as multipotent CD34+ HPSCs. The most frequent mutations concern driver genes such as JAK2 and non-driver genes such as ASXL1 , IDH1/2 , SRSF2 , EZH1 [ 41 ]. Further studies confirm a similar mutational profile in circulating free DNA (cfDNA) and in paired granulocyte DNA obtained from the plasma of PMF patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Farina et al aimed to isolate CECs in primary myelofibrosis patients to compare their mutation spectrum with blood cells from the same individuals. They discovered the JAK2 mutation in a subset of patients' CECs and identified common myeloid-associated mutations between CECs and haematopoietic stem and progenitor cells, including ASXL1, TET2, and SRSF2 [52,53]. However, these findings are limited by the small patient cohort and the low sensitivity of the next generation sequencing method.…”
Section: Circulating Endothelial Cells and Cancer Diseasesmentioning
confidence: 99%
“…Starting from this hypothesis, a recent study compared the mutational profiles of hematopoietic progenitor cells and circulating endothelial cells in patients with PMF. It showed that the JAK2 mutation is present in both cell populations, suggesting that endothelial circulating cells could play an important role in the pathogenesis and progression of PMF, as well as the associated vascular complications [21].…”
Section: The Link Between Mpd and Choreamentioning
confidence: 99%